THE IMPLEMENTATION OF GRICE’S MAXIMS OF THE COOPERATIVE PRINCIPLE IN COMMUNICATION: https://doi.org/10.5281/zenodo.20823185 - Drozdova, Tatiana (Scientific practical conference, 2026)
The article touches upon the role of the cooperative principle in the process of speech interaction. To succeed participants should take into this principle in the process of speech interaction. On the assumption four categories under one or another of which will fall certain more specific maxims and submaxims that may be distinguished.